IMPLEMENTASI PERATURAN BUPATI KUANTAN SINGINGI NOMOR 74 TAHUN 2020 TENTANG RENCANA AKSI DAERAH DALAM PENGURANGAN DAN PENGHAPUSAN MERKURI DI KABUPATEN KUANTAN SINGINGI TAHUN 2020-2023 (Studi Kasus Kecamatan Kuantan Hilir Seberang) - Jannah, Riskotul; Rafi, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study discusses how to implement the Kuantan Singingi Regent Regulation Number 74 of 2020 concerning the Regional Action Plan for the Reduction and Elimination of Mercury. The problem in this study is that there are still many activities of Unlicensed Gold Miners (PETI) that use mercury in Kuantan Hilir Seberang District. Furthermore, Unauthorized Gold Miners (PETI) who use Mercury have resulted in river flow pollution in Kuantan Hilir Seberang District. This research uses a qualitative method through descriptive analysis This research aims to analyze the implementation of Regent Regulation Number 74 of 2020 concerning the Regional Action Plan for Mercury Reduction and Elimination. The theory of policy implementation used as the basis of analysis is the theory of Merilee S. Grindle, which emphasizes that the success of implementation is influenced by two main variables, namely the content of policy and the context of implementation. The results of the study show that the implementation of this policy has not been running optimally. In terms of policy content, it was found that the implementation apparatus, especially the Environment Agency, did not have adequate technical and administrative readiness. This unpreparedness is reflected in the unavailability of training, lack of understanding of the substance of the policy, and the absence of technical implementation instructions as an operational reference. Meanwhile, from the aspect of the implementation environment, the main obstacles lie in the limitation of budget allocation, weak cross-sector coordination between implementing agencies, and low commitment of implementers at the technical and structural levels. Keywords: Policy Implementation, Unlicensed Gold Mining (PETI), Mercur